Intensity‐modulated radiotherapy versus proton radiotherapy versus carbon ion radiotherapy for spinal bone metastases: a treatment planning study. (8th November 2015) - Rief, Harald; Chaudhri, Naved; Tonndorf‐Martini, Eric; Bruckner, Thomas; Rieken, Stefan; Bostel, Tilman; Förster, Robert; Schlampp, Ingmar; Debus, Jürgen; Sterzing, Florian
Abstract : Outcomes for selected patients with spinal metastases may be improved by dose escalation using stereotactic body radiotherapy (SBRT). As target geometry is complex, we compared SBRT plans using step‐and‐shoot intensity‐modulated radiotherapy (IMRT), carbon ion RT, and proton RT. We prepared plans treating cervical, thoracic, and lumbar metastases for three different techniques — IMRT, carbon ion, and proton plans — to deliver a median single 24 Gy fraction such that at least 90% of the planning target volume (PTV) received more than 18 Gy and were compared for PTV coverage, normal organ sparing, and estimated delivery time. PTV coverage did not show significant differences for the techniques, spinal cord dose sparing was lowered with the particle techniques. For the cervical lesion spinal cord maximum dose, dose of 1% (D1), and percent volume receiving 10 Gy ( V 10 Gy ) were 11.9 Gy, 9.1 Gy, and 0.5% in IMRT. This could be lowered to 4.3 Gy, 2.5 Gy, and 0% in carbon ion planning and to 8.1 Gy, 6.1 Gy, and 0% in proton planning. Regarding the thoracic lesion no difference was found for the spinal cord. For the lumbar lesion maximum dose, D1 and percent volume receiving 5 Gy ( V 5 Gy ) were 13.4 Gy, 8.9 Gy, and 8.9% for IMRT; 1.8 Gy, 0.7 Gy, and 0% for carbon ions; and 0   Gy, < 0.01   Gy, and 0% for protons. Estimated mean treatment times were shorter in particle techniques (6–7 min vs. 12–14 min with IMRT). This planning study indicates that carbon ion and proton RT can deliver high‐quality PTV coverage for complex treatment volumes that surround the spinal cord. PACS number: 87.55.dk